Victor Grant Collection, Album 4, Photograph 258 Grandma Livingston, John and Eva Livingston, Auntie McQueen
Informal full length photograph, taken outside.
Designated 5.258 in listing stands for Album 5, Photograph 258.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Livingston, John; Livingston, Eva W; Livingston family. -- New Mexico; Genealogy - Photographic collection